Crowdfunding as a Tool for Promotion and Development of Tourism-related Innovation Projects - DZHANDZHUGAZOVA, Elena A.; ILINA, Elena L.; LATKIN, Aleksander N.; BLINOVA, Ekaterina A.; ROMANOVA, Marianna M. (Journal of Environmental Management and Tourism, 2017)
The topicality of the set problem is explained by the fact that technological capabilities for new information grounds for implementation of creative and social projects based on crowdfunding are created within modern conditions of the development of innovation economy. The goal of the article is to study the problems of the development of tourism-related innovation projects based on the most active crowdfunding platforms allowing not only to raise funding but to spread information on the projects online including social media. The principal methods of the study of the set problem are methods of desk social study and modelling allowing to identify, using the analysis of the results, the most active crowdfunding platforms functioning in the Russian Federation and typical structure of crowdfunding projects approved by investors. The article presents main reasons hindering the development of Russian crowdfunding and offers the ways of overcoming them. On the basis of the comparative analysis of Boomstarter.ru crowdfunding projects of 2013-2016 we make a conclusion that despite a small share of tourism-related crowdfunding projects they have high average values of key figures, which shows their success and adequacy. The materials of the article may be useful for representatives of research and education community dealing with the study of innovation economy and tourist industry problems as well as for practitioners of travel and hospitality industry.